Systematic Position of Miyakea Integrifolia Miyabe & Tatew. In the Infrageneric Classification of Pulsatilla (Ranunculaceae): Palynological Challenges (Bangladesh Journal of Plant Taxonomy, 2024)
Abstract not available.Bangladesh J. Plant Taxon. 31(1): 187-195, 2024 (June)